The yield and grain composition of naked oat grown with spring vetch as an undersown plant - Pisulewska, Elzbieta; Klima, Kazimierz; Pisulewski, Pawel M. (MTT, 2004)
Growing cereal-legume mixtures is associated with N transfer from the legume to the accompanying cereal and offers the potential for reducing the amount of N-fertiliser used in cereal grain production. Cereal crops grown in these mixtures tend to accumulate more protein in their grain. At the same time they extend their growing season. The traditional oat production system in Poland is based on covered oats grown with vetch on poor and damp soils. Our objective was to determine the grain yield and quality of a naked oat cultivar grown as a pure crop and with a spring vetch companion crop. The field experiment was conducted at the Czyrna Experimental Station from 1999 to 2002. The naked oat cv. Akt was sown either as a pure crop or with spring vetch determinate cv. Ina at two seed rates. The amount of rainfall over the experimental years varied from 737 to 1040 mm, corresponding with the multiannual average of 834 mm. The effect of graded seed rates of spring vetch on yield and gross chemical composition of naked oat grain (AOAC, 1995) and ?-glucans content (the Megazyme assay kit no 995.16) were determined. The present results confirm earlier findings indicating that total yields of wheat and triticale grown with legume companion plants were decreased with decreasing cereal seeding rates (Pisulewska, 1997). Cereal grain protein content was increased with increasing seeding rates of legume companions. We confirmed the negative relationship between oat grain protein and fat content, while ash and ?-glucans were only little, although significantly affected. In conclusion, the relative changes in grain yield and quality of naked oat grown either as a pure crop or with a spring vetch companion plant, were similar to those observed for wheat and triticale. AOAC, 1995. "Official Methods of Analysis of AOAC International" (16th ed.), AOAC International: Arlington, Virginia. USA; Pisulewska, E. 1997. D.Sc. Thesis, Agricultural University of Kraków. Poland.
Keywords: Ka; naked oat; legume companion; grain yield; composition